Późnorzymska chata ze stanowiska 2 w Tokarni, gm. Chęciny, woj. kieleckie - Lechowicz, Zbigniew (Acta Universitatis Lodziensis. Folia Archaeologica, 1983)
In the course of studies of a Late-Roman settlement at excavation site No. 2 at Tokarnia there was exposed a relic of a big cottage (excavation 2, cottage No.1). In this article the author performs an analysis of the cottage equipment with a special attention focussed on ceramic vessels. This allows the author to carry out a functional division of the obtained set of ceramic vessels. Their comparison with storage dens points out that they were playing an essential role in storage of granular products including grains. The internal division of the object is attributed by the author to specialized cloth-weaving production. The analyzed object is dated to the first half of 5th century A.D.